Pengaruh modul self regulated learning terhadap prokrastinasi akademik dan keterampilan berpikir kritis mahasiswa PGSD UNS - Endah Yuliana Lestari; Idam Ragil Widianto Atmojo; Roy Ardiansyah (Didaktika Dwija Indria, 2023)
Abstract. The study aims to determine the effect of self-regulated learning modules on academic procrastination and critical thinking skills of college students in PGSD UNS. The type of research is experimental research with a quasi design. The research population was PGSD UNS students with a sample of 67 students. Samples were divided into an experimental class and a control class. The class that became the experimental class was 2E with a total of 34 students, while the class that became the control class was 2F with a total of 33 students. Content validity using Aikens V states all instruments are valid. The reliability instruments using Alpha Cronbach's stated that all instruments were reliable with a coefficient value of 0.833 on the academic procrastination scale and 0.713 for the critical thinking test. Hypothesis Test using Manova Test Multivariate Analysis. The Manova test shows a significance value of 0.000 <0.05. The conclusion is that there is an influence of the self-regulated learning module on academic procrastination and critical thinking skills of PGSD UNS students.